Sidonio Apollinare e il ‘senato in esilio’: intorno a una metafora poetica ‘repubblicana’ - Gusso, Massimo (Lexis, 2021)
The Gallo-Roman imperial accession of Avitus, following the Vandal plunder, is presented by Sidonius Apollinaris (Carm. 7) as an effective opportunity for the revival of the Western empire in a utopian and mythical-historical perspective, which uses repertoires of Roman Republican History. An neglected tradition of that same history is thus revived, incidentally, with precedents ranging from the Gallic siege to civil wars and beyond. In this context, some senatorial ateliers where communications functional to the idea of a senate “free from the emperor” were experimented, could have made use of a certain “republican” modality of the use of prodigies in the most unscrupulous way, with recourse to even very complex propaganda paradigms.